Exposure Assessment to Persistent Organic Pollutants in Wildlife: The Case Study of Coatzacoalcos, Veracruz, Mexico - Espinosa-Reyes, Guillermo; González-Mille, Donaji J.; Ilizaliturri-Hernández, César A.; Martínez, Fernando Díaz-Barríga; Mejía-Saavedra, Jesús (IntechOpen, 2012)
None